Circonscript subcutaneous arteriovenous malformation of the head - Mirchevski, Vladimir; Zogovska, Elizabeta; Chaparoski, Aleksandar; Filipce, Venko; Kostov, Milenko; Mirchevski, Mirko Mishel (Macedonian Academy of Sciences and Arts / De Gruyter, 2017)
The aim of this study is to show the various possibilities to treat this rare malformation, accentuating the results of the early surgical treatment before complications. Material: The authors present 8 cases of patients with subcutaneous arteriovenous malformations, 5 females and 3 males (age of 7, 13, 19, 23, 27, 52 and 58 years) treated in the period of 1999 until 2015 at the Clinic for Neurosurgery and the Clinic for Plastic, Aesthetic and Reconstructive Surgery in Skopje, Republic of Macedonia. This malformation has been observed by the parents in the childhood, around the age of 3 years in all cases. Local red circonscripted nodule, soft, with manually discharging tendency and varicose dilated veins have been observed in all cases, deaf on both sides in one case, while in the older case, a cavernous sinus thrombosis caused unilateral exophthalmia, hyaline indurated ophthalmic vein, vertigo, arrhythmia, heart failure and bradypsychia have been observed. The size of the malformation has been from 2.5 to 7 cm. The diagnostics was done using CT, CT-angiography and digital angiography including external carotid angiography. Endocranial arterials peduncle was present in all cases. Results: Six cases underwent surgery, while two cases were treated with several treatments of endovascular embolization. The follow up has been ranged from 2 to 15 years. All surgically treated patients improved without recurrence, the exophthalmia, bradypsychia and the heart problems regressed, while in patients treated with endovascular non-complete occlusion the AVM decreased, but still remained. In conclusion: The Surgical treatment remains a first option if it is possible, and as earlier as possible, while embolization is a useful tool in cases where a complete excision is not possible.
ЦИРКОНСКРИПТНИ ПОТКОЖНИ АРТЕРИОВЕНСКИ МАЛФОРМАЦИИ НА ГЛАВАТА
Keywords: subcutaneous AVM; surgery